(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this study , we define the concepts of inverse operation , identity element , inverse element , special identity element , λ-group ( special group ) , λ-ring ( special ring ) , λfield ( special field )